2014
DOI: 10.1111/raq.12068
|View full text |Cite
|
Sign up to set email alerts
|

Rearing European brown shrimp (Crangon crangon, Linnaeus 1758): a review on the current status and perspectives for aquaculture

Abstract: The European brown shrimp, Crangon crangon, is a highly valued commercial species fished in the north-eastern Atlantic, especially the North Sea. The shrimp fisheries are mainly coastal and exert high pressures on the local ecosystems, including estuaries. The culture of the species provides an alternative to supply a niche market (large live/fresh shrimps) in a sustainable manner. However, after more than a century of biological research on this species, there is still little knowledge on its optimal rearing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 105 publications
(138 reference statements)
0
6
0
Order By: Relevance
“…Historically, experiments with C. crangon larvae have not examined density as a factor (Delbare et al, ). The effect of individual and mass rearing (24–100 individuals L ‐1 ) was examined by Criales and Anger (); they concluded that high larval rearing densities resulted in a higher frequency of stunted forms, while mortality rates did not differ between individual and mass rearing.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Historically, experiments with C. crangon larvae have not examined density as a factor (Delbare et al, ). The effect of individual and mass rearing (24–100 individuals L ‐1 ) was examined by Criales and Anger (); they concluded that high larval rearing densities resulted in a higher frequency of stunted forms, while mortality rates did not differ between individual and mass rearing.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, experiments with C. crangon larvae have not examined density as a factor (Delbare et al, 2015). to a benthic lifestyle during metamorphosis to the post-larval stage (Campos & Van der Veer, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations